PENGEMBANGAN MODEL MODUL PEMBELAJARAN BAHASA INDONESIA BERBASIS INVESTIGASI KELOMPOK (GROUP INVESTIGATION) PADA MATERI MENULIS KARANGAN ILMIAH SISWA KELAS XI SMA N 8 PADANG - Ninit Alfianika; Atmazaki .; Abdurahman . (Fakultas Bahasa dan Seni UNP, 2014)
Abstract: This study aims to produce a valid, practical, and effective Indonesian learning modules model with group based investigation in writing scientific essay which can be used by students of XI IPA 4 at SMA N 8 Padang. This type of research was the development of research with using 4D model of development. Development phase began with defining, designing, and ends with the development. Based on the data analysis and discussion it can be summarized as follows. First, the validity of the Indonesian learning modules model with group based investigation in writing scientific article is considered as valid. Second, the practicalities Indonesian learning modules model with group based investigation in writing scientific article is considered as very valid. Third, the effectiveness of Indonesian learning modules model with group based investigation in writing scientific article is considered as very effective. Thus, modules that have been developed can be used as teaching materials in the Indonesian language learning, especially for writing scientific articles. Kata kunci: modul pembelajaran; berbasis group investigation; materi karanngan ilmiah.